Pelatihan Pembelajaran Menggunakan Augmented Reality bagi Kepala sekolah/Guru - Fathiah; Zahriah; Nazaruddin Ahmad; Dewi, $arini Vita; maisura; Mursyidin (JKA, 2024)
This dedication activity was carried out at the Aula Hotel Linge, Takengon, central Aceh, Indonesia with the target target being the head of the first and upper secondary school level in the district of Central Aceh. This dedication aims to train school leaders and teachers in the use of augmented reality (AR) based learning media. The Augmented Reality application can display 3D objects in the real world through virtual displays, allowing users to interact with virtual objects. This training uses training methods. In this dedication training practice it was found that the head of the school and the teacher better understand the use of augmented reality-based learning media (AR) through increased assembler applications before and after the given training practice. The increase can be seen from the comparison of pre-test and post-test values given at the time of the activity.